Restorative justice-based criminal case resolution in Salatiga, Indonesia: Islamic law perspective and legal objectives - Ariefulloh Ariefulloh; Hibnu Nugroho; Angkasa Angkasa; Riris Ardhanariswari (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
Restorative justice is a pattern of dispute resolution which emphasizes the responsibility of the perpetrator for the consequences of his actions while at the same time paying attention to the position of the victim. This is not simply about punishing the offender; it is about obtaining justice through discussion outside of the criminal justice system to ensure the situation can be returned to its prior state. Islamic law offers a concept of restorative justice called islah, which is a technique to resolve conflicts between parties by forgiving one another. Salatiga City, the most tolerant city in Indonesia, is where this study is being conducted. The idea of restorative justice is used to resolve disputes through the role of a lurah (head of neighborhood), who is responsible for upholding communal order. It is intriguing to investigate whether the reality of restorative justice in Salatiga City can achieve the three main objectives of the law as outlined by Gustav Radburch: justice, benefit, and legal certainty. This study employs a qualitative methodology and a socio-legal research design. Interviews with the offenders, victims, and the lurah who served as the government's mediator resulted in the gathering of data. The findings of this study demonstrate that Salatiga City's restorative justice method to conflict settlement has achieved the goals of justice and legal advantage and can even foster good will among the parties. The absence of lurah's legal standing in the resolution of this issue, however, does not satisfy the requirement of legal clarity. For Salatiga City residents, a legal foundation is required for restorative justice-based legal dispute settlement